Physical property anisotropy of foliated fault rocks: Study from the Nobeoka Thrust, Shimanto Belt, southwest Japan. (30th May 2018) - Hamahashi, Mari; Tanikawa, Wataru; Hamada, Yohei; Hashimoto, Yoshitaka; Saito, Saneatsu; Kimura, Gaku
Abstract: To investigate the physical property anisotropies of foliated fault rocks in subduction zones, the hanging wall phyllites and footwall cataclasites exhumed along the Nobeoka Thrust, a fossilized out‐of‐sequence‐thrust in the Shimanto Belt, Japan, was focused. Discrete physical property (electric resistivity, P‐ and S‐wave velocities, and porosity) measurements were conducted employing geologic coordinates (depth‐parallel direction, strike direction, and maximum dip direction of foliation), using the core samples obtained from the Nobeoka Thrust Drilling Project and compared the data to borehole geophysical logs. A higher sample P‐wave velocity ( Vp ), lower S‐wave velocity ( Vs ), higher Vp / Vs, and lower sample porosity and resistivity compared to the logs, are inferred to have been caused by the larger sampling scale of the logs and lower fluid saturation of the borehole. The phyllites and cataclasites exhibited substantial vertical and horizontal anisotropy of Vp (0.4–17.3 % and 2.7–13.8 %, respectively), Vs (0.5–56 % and 7.7–43 %, respectively), and resistivity (0.9–119 % and 2.0–65.9 %, respectively). The physical property anisotropies are primarily affected by the dip angles of foliation. The fault rocks that have gentler dip angles exhibit a higher Vp in the strike and maximum dip direction and a lower Vp in the depth‐parallel direction. In contrast, the fault rocks that have steeply dipping structures show a higher Vp in the strike and depth‐parallel directions with a lower velocity in the maximum dip direction. Resistivity anisotropy show a trend opposite to that of the Vp in relation to the dip angles. Our results show lower Vp anisotropy than those obtained in previous studies, which measured wave speeds perpendicular or parallel to foliation under confining pressure. This study highlights the significance of dip angles on vertical properties in geophysical surveys across foliated fault rocks. Abstract : To investigate the physical property anisotropies of foliated fault rocks along the Nobeoka Thrust, we conducted discrete resistivity, P‐ and S‐wave velocity and porosity measurements in three‐dimensional geologic coordinate. The phyllites and cataclasites exhibit substantial vertical and horizontal anisotropy of Vp (0.4–17.3 % and 2.7–13.8 %, respectively), Vs (0.5–56 % and 7.7–43 %, respectively), and resistivity (0.9–119 % and 2.0–65.9 %, respectively), inferred to be primarily affected by the dip angles of foliation.